GCAP1 rescues rod photoreceptor response in GCAP1/GCAP2 knockout mice - Howes, Kim A. (Oxford University Press, 2002)
Visual transduction in retinal photoreceptors operates through a dynamic interplay of two second messengers, Ca(2+) and cGMP. Ca(2+) regulates the activity of guanylate cyclase (GC) and the synthesis of cGMP by acting on a GC-activating protein (GCAP). While this action is critical for rapid termination of the light response, the GCAP responsible has not been identified. To test if GCAP1, one of two GCAPs present in mouse rods, supports the generation of normal flash responses, transgenic mice were generated that express only GCAP1 under the control of the endogenous promoter. Paired flash responses revealed a correlation between the degree of recovery of the rod a-wave and expression levels of GCAP1. In single cell recordings, the majority of the rods generated flash responses that were indistinguishable from wild type. These results demonstrate that GCAP1 at near normal levels supports the generation of wild-type flash responses in the absence of GCAP2.